Dietary Intakes Differ by Body Composition Goals: An Observational Study of Professional Rugby Union Players in New Zealand. Issue 6 (December 2019) - Black, Katherine E.; Hindle, Chloe; McLay-Cooke, Rebecca; Brown, Rachel C.; Gibson, Claire; Baker, Dane F.; Smith, Brett
Preseason in rugby union is a period of intensive training where players undergo conditioning to prepare for the competitive season. In some cases, this includes modifying body composition through weight gain or fat loss. This study aimed to describe the macronutrient intakes of professional rugby union players during pre-season training. It was hypothesized that players required to gain weight would have a higher energy, carbohydrate and protein intake compared to those needing to lose weight. Twenty-three professional rugby players completed 3 days of dietary assessment and their sum of eight skinfolds were assessed. Players were divided into three groups by the team coaches and medical staff: weight gain, weight maintain and weight loss. Mean energy intakes were 3, 875 ± 907 kcal·d −1 (15, 965 ± 3, 737 kJ·d −1 ) (weight gain 4, 532 ± 804 kcal·d −1 ; weight maintain 3, 825 ± 803 kcal·d −1 ; weight loss 3, 066 ± 407 kcal·d −1 ) and carbohydrate intakes were 3.7 ± 1.2 g·kg −1 ·d −1 (weight gain 4.8 ± 0.9 g.kg −1 ·d −1 ; weight maintain 2.8 ± 0.7 g·kg −1 ·d −1 ; weight loss 2. 6 ± 0.7 g·kg −1 ·d −1 ). The energy and carbohydrate intakes are similar to published intakes among rugby union players. There were significant differences in energy intake and the percent of energy from protein between the weight gain and the weight loss group.